Mechanics of materials - Gere, James M (Brooks/Cole-Thomas Learning, 2004)
The sixth edition of mechanics of materials continues its legacy as the classic, definitive textbook for solid mechanics. This new edition has been edited and polished for clarity throughout, while care has been taken to preserve the highly praised features of the earlier editions. The text maintains an emphasis on presenting the fundamental concepts and applications of mechanics of materials in a manner that develops student understanding along with analytical and problem-solving skills.